Usefulness of MR imaging-derived thermometry and dosimetry in determining the threshold for tissue damage induced by thermal surgery in rabbits - McDannold, N J; King, R L; Jolesz, F A; Hynynen, K H (Radiology, 2000)
To investigate in vivo the feasibility of using magnetic resonance (MR) imaging-derived temperature and thermal dose measurements to find the threshold of thermal tissue damage. Sonications were delivered in rabbit thigh muscles at varying powers. Temperature-sensitive MR images obtained during the sonications were used to estimate the temperature and thermal dose. The temperature, thermal dose, and applied power were then correlated to the occurrence of tissue damage observed on postsonication images. An eight-element phased-array transducer was used to produce spatially flat temperature profiles that allowed for averaging to reduce the effects of noise and the voxel size. The occurrence of tissue damage correlated well with the MR imaging-derived temperature and thermal dose measurements but not with the applied power. Tissue damage occurred at all locations with temperatures greater than 50.4 degrees C and thermal doses greater than 31.2 equivalent minutes at 43.0 degrees C. No tissue damage occurred when these values were less than 47.2 degrees C and 4.3 equivalent minutes. MR imaging thermometry and dosimetry provide an index to predict the threshold for tissue damage in vivo. This index offers improved online control over minimally invasive thermal treatments and should allow for more accurate target volume coagulation.